2013
DOI: 10.1002/hlca.201200622
|View full text |Cite
|
Sign up to set email alerts
|

N‐Bearing Furanone Derivatives from an Endophytic Fungus in Huperzia serrata

Abstract: Two new polyketide derivatives, huaspenones C and D (1 and 2, resp.), were isolated from the cultures of an endophytic fungus Peyronellaea sp. HS-12, derived from the stems of Huperzia serrata. They share N-bearing furan-3(2H)-one backbone, and 2 has an unprecedented furo[3,2-c]pyridine skeleton. Their structures including the absolute configuration were elucidated by extensive spectroscopic analysis combined with quantum-chemical calculations. (2E,4E)-6-hydroxy-2-methylocta-2,4dienoic acid (3), a key intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The 1 H and 13 C NMR data (Table 1) of 1 displayed the presence of a characteristic for a carboxyl (δ C 169.2), a sp 2 quaternary carbon (δ C 126.2), three olefinic methine groups (δ H/C 6.21/143.2, 7.10/137.5, 6.54/124.8), two oxygenated methylene groups (δ H/C 3.88/75.3, 3.49/69.7) and two methyl groups (δ H/C 1.04/19.2, 1.84/12.5). The above data were similar to those of the known compound (2E,4E)-6hydroxy-2-methylocta-2,4-dienoic acid, [15] except for an additional oxygenated methylene carbon signal and the absence of a methine carbon signal. Based on the proton spin coupling system in the 1 H-1 H COSY spectrum (Figure 2) of H 3 -8/H-7/H-6/ H-5/H-4/H-3, the connection fragment from C-3 to C-8 was established.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The 1 H and 13 C NMR data (Table 1) of 1 displayed the presence of a characteristic for a carboxyl (δ C 169.2), a sp 2 quaternary carbon (δ C 126.2), three olefinic methine groups (δ H/C 6.21/143.2, 7.10/137.5, 6.54/124.8), two oxygenated methylene groups (δ H/C 3.88/75.3, 3.49/69.7) and two methyl groups (δ H/C 1.04/19.2, 1.84/12.5). The above data were similar to those of the known compound (2E,4E)-6hydroxy-2-methylocta-2,4-dienoic acid, [15] except for an additional oxygenated methylene carbon signal and the absence of a methine carbon signal. Based on the proton spin coupling system in the 1 H-1 H COSY spectrum (Figure 2) of H 3 -8/H-7/H-6/ H-5/H-4/H-3, the connection fragment from C-3 to C-8 was established.…”
Section: Resultssupporting
confidence: 81%
“…As part of our research on discovering structurally novel enzyme inhibitors from mangrove fungi, [10][11][12][13] the fungus strains of Trichoderma harzianum SCSIO 41051, obtained through in situ culture [14] in mangrove sediment, collected from Gaoqiao mangrove wetland in the Zhanjiang coastline of the northern part of Beibu Gulf. Further chemical investigations of their crude extract led to the isolation of 17 compounds, including a new fatty acid derivative (1), night known polyketides (2-10), five known alkaloids (11)(12)(13)(14)(15), and two known sesquiterpenoids (16 and 17) (Figure 1). The in vitro enzyme inhibitory assay showed that compounds 9 and 14 exhibited moderate AChE inhibitory activities and compounds 8 and 9 displayed moderate inhibition on PL.…”
Section: Introductionmentioning
confidence: 99%
“…Budziszewska and Szypuła 2010 ; Chen et al 2011 ; Wang et al 2011 ), and two have been driven by an interest in identifying possible novel bioactive chemical compounds (e.g. Zhu et al 2010 ; Xiang et al 2013 ). Indeed, some endophytic fungi from lycophyte Huperzia serrata that is used in chinese medicine are known to produce bioactive metabolites such as huaspenones, (Xiang et al 2013 ) or huperzine (see Zhu et al 2010 ; Zhang et al 2011 , and literature therein).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 2010 ; Xiang et al 2013 ). Indeed, some endophytic fungi from lycophyte Huperzia serrata that is used in chinese medicine are known to produce bioactive metabolites such as huaspenones, (Xiang et al 2013 ) or huperzine (see Zhu et al 2010 ; Zhang et al 2011 , and literature therein). Only two studies, by Holm and Holm ( 1981 ) and by Engelhardt ( 1987 ), have been dedicated studying the fungal communities of above-ground organs of Lycopodiaceae.…”
Section: Introductionmentioning
confidence: 99%
“…and is the first naturally occurring N-bearing furanone derivative reported in nature. This study represents the second report of its kind [ 74 ].…”
Section: Discussionmentioning
confidence: 99%